Characterization of flow interactions in an axial fan stage. Issue 12 (18th September 2020) - Ghenaiet, Adel
Abstract: The aim of this study is to characterize the steady and unsteady flows of a high‐speed axial fan stage and assess its aerodynamic performance parameters. The flow unsteadiness is related to the stator‐rotor interaction originated mainly by two mechanisms: the first is attributed to the potential effect and the second to the wake‐blade interaction and the mixing through the blades' passages. Such effects are dependent on the circumferential positions of blades and inter‐distance between stator and rotor, which could be alleviated by understanding these flow interactions. The pressure waves' main diametrical modes (two blades interacting with two vanes) and their sequences are predicted analytically. FFT analysis of the computed static pressure fluctuations at different monitor points allowed identifying the prevailing modes of interaction and their frequencies and sequence. The assessment of inter‐distance is an important step toward identifying the detrimental effects of axial interdistance on the aerodynamic performance. The closer the blade‐rows of this fan stage can be spaced, the more compact the cooling system of an automotive could be designed. Abstract : There are mainly two mechanisms of IGVs and rotor blades interactions identified: The first is attributed to the potential effect whereas the second is due to the wake‐blade interaction and the advection of wake mixing into blades' passages. These effects depend on the circumferential positions of blades and axial inter‐distance between stator and rotor. The computed steady performance parameters are overstimated since the flow solution is obtained at one particular relative position of blade causing miscalculation of blade loading and losses.